Knowledge, experience and practices of optometrists in Uganda about keratoconus - Godfrey Wanok; Simon Arunga; Baljean Dhillon; Naomi Nsubuga (African Vision and Eye Health)
Background: Keratoconus has a global prevalence of 0.2 to 4790 per 100 000 persons and there is currently no published report about its incidence, prevalence or the role of optometrists in its management in Uganda. This study looked at the role of optometrists in the diagnosis, management and referral of patients with keratoconus in Uganda.